Antibiotic prophylaxis in cirrhosis patients with upper gastrointestinal bleeding: An updated systematic review and meta‐analysis. Issue 3 (20th December 2022) - Wong, Yu Jun; Tan, Chin Kimg; Yii, Yuen Lin; Wong, Yoko; Tam, Yew Chong; Chan, Edwin; Abraldes, Juan G.
Abstract: Objective: Emerging evidence suggest that antibiotic prophylaxis may be omitted in early cirrhosis patients with upper gastrointestinal bleeding (UGIB), which question the benefits of antibiotic prophylaxis on rebleeding, mortality related to ongoing bleeding, and the need for salvage therapy. As the management of UGIB has improved over time since the last review a decade ago, we performed an updated meta‐analysis to review the benefits of antibiotic prophylaxis in cirrhosis patients with UGIB. Method: Six electronic databases including PubMed/MEDLINE, EMBASE, Scopus, Web of Science, Cochrane library, and ClinicalTrial.gov were systematically searched up to December 1, 2021. The primary outcome was 6 weeks mortality. Secondary outcomes include the risk of infection, rebleeding at 7 days and 6 weeks, mortality related to ongoing bleeding, need for salvage therapy, and infection‐related mortality. Result: Eighteen studies (12 randomized controlled trials [RCT], 6 non‐RCT) from 3180 subjects were identified among 2129 citations. Antibiotic prophylaxis reduces mortality at 6 weeks, risk of infection, and infection‐related mortality (pooled relative risk: 0.72, 0.39, and 0.41, respectively). Although antibiotics reduce the risk of rebleeding and the amount of blood transfusion, they did not reduce the risk of mortality from ongoing bleeding nor the need for salvage therapy. Antibiotic prophylaxis may shorten the length of stay in the intensive care unit. Conclusion: Antibiotic prophylaxis reduces rebleeding, 6‐week mortality, and infection‐related mortality. Due to the low risk of infection and death, dedicated studies are warranted to evaluate the benefit of antibiotic prophylaxis in early cirrhosis with UGIB. Highlights: Our updated meta‐analysis reaffirms the benefit of antibiotic prophylaxis in reducing the mortality at 6 weeks, risk of infection, and infection‐related mortality. Although antibiotics reduce the risk of rebleeding and the amount of blood transfusion, they did not reduce the risk of mortality from ongoing bleeding nor the need for salvage therapy. Antibiotic prophylaxis may reduce the length of stay in the intensive care unit. Dedicated studies are required to study the benefit of prophylactic antibiotic among early cirrhosis patients with upper gastrointestinal bleeding.